Robust skin-integrated conductive biogel for high-fidelity detection under mechanical stress - Tian Li; Haobo Qi; Cancan Zhao; Zhenming Li; Wei Zhou; Guanjin Li; Hao Zhuo; Wei Zhai (Nature Communications)
Abstract Soft conductive gels are essential for epidermal electronics but often face challenges when interfacing with uneven surfaces or areas with extensive hair, especially under mechanical stress. In this study, we employed the concept of liquid-to-solid transformation to enhance integration at biointerfaces and designed an in-situ biogel capable of rapidly transitioning between liquid and solid states within 3 min via a temperature switch. The biogel features a semi-interpenetrating polymer network design and dual conduction pathways, resulting in high tensile strength (~1–3 MPa), a skin-compatible modulus (~0.3–1.1 MPa), strong skin adhesive strength (~1 MPa), and superior signal-to-noise ratio (SNR, ~30–40 dB). The biogel demonstrates significant performance in mechanically demanding environments, showing potential for accurately capturing outdoor exercise data, monitoring muscle recovery from sports-induced fatigue, and in vivo monitoring of cardiac physiological signals. The liquid-to-solid transformation concept, coupled with the design strategy for highly integrated and stable soft conductive materials, provides a basis for advancing conductive interface designs for high-fidelity signal acquisition.